2007
DOI: 10.1105/tpc.106.047506
|View full text |Cite
|
Sign up to set email alerts
|

Theindeterminate gametophyte1Gene of Maize Encodes a LOB Domain Protein Required for Embryo Sac and Leaf Development

Abstract: Angiosperm embryo sac development begins with a phase of free nuclear division followed by cellularization and differentiation of cell types. The indeterminate gametophyte1 (ig1) gene of maize (Zea mays) restricts the proliferative phase of female gametophyte development. ig1 mutant female gametophytes have a prolonged phase of free nuclear divisions leading to a variety of embryo sac abnormalities, including extra egg cells, extra polar nuclei, and extra synergids. Positional cloning of ig1 was performed base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(194 citation statements)
references
References 59 publications
3
182
1
3
Order By: Relevance
“…For many Arabidopsis LBD genes, loss-offunction mutation phenotypes were not apparent with the exception of LBD6, which performs a role in leaf development (Semiarti et al, 2001;Xu et al, 2003). However, several loss-of-function mutants of rice and maize LBD genes have been reported to evidence clear phenotypes (Inukai et al, 2005;Liu et al, 2005;Bortiri et al, 2006;Evans, 2007;Taramino et al, 2007). The ectopic expression of several LBD genes, as wild type or as proteins fused to a transcriptional repression domain, yielded morphological phenotypes, provid- ing clues to the biological functions of these LBD genes (Shuai et al, 2002;Chalfun-Junior et al, 2005;Borghi et al, 2007;Okushima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For many Arabidopsis LBD genes, loss-offunction mutation phenotypes were not apparent with the exception of LBD6, which performs a role in leaf development (Semiarti et al, 2001;Xu et al, 2003). However, several loss-of-function mutants of rice and maize LBD genes have been reported to evidence clear phenotypes (Inukai et al, 2005;Liu et al, 2005;Bortiri et al, 2006;Evans, 2007;Taramino et al, 2007). The ectopic expression of several LBD genes, as wild type or as proteins fused to a transcriptional repression domain, yielded morphological phenotypes, provid- ing clues to the biological functions of these LBD genes (Shuai et al, 2002;Chalfun-Junior et al, 2005;Borghi et al, 2007;Okushima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among these are four transcripts encoding known stem cell regulators, including three CLASS I KNOX genes and a GATA domain protein homologous to HANABA TARANU in Arabidopsis (Figures 4C and 4D; see Supplemental Data Set 8 online) Zhao et al, 2004;Mukherjee et al, 2009;reviewed in Hay and Tsiantis, 2010). Upregulated transcripts encoding proteins that function in organogenesis and cell proliferation of lateral organs include WUSHEL-RELATED HOMEOBOX3A (WOX3A), the YABBY gene DROOPING LEAF2 (DL2), the lateral organ boundary gene INDETERMINATE GA-METOPHYTE1 (IG1), and two GRF-LIKE transcripts (Kim et al, 2003;Nardmann et al, 2004;Yamaguchi et al, 2004;Evans, 2007;Nardmann et al, 2007;Zhang et al, 2007;Zhang et al, 2008). In addition to three AUXIN RESPONSE FACTOR (ARF) class transcription factors, several transcripts that encode hormone biosynthetic proteins are also upregulated in stage 14 SAMs, including seven gibberellin metabolic transcripts implicated in lateral organ growth and development.…”
Section: Morphological and Molecular Maturation Of The Maize Sammentioning
confidence: 99%
“…Members of this gene family can be divided into different classes and subtypes, which are involved in distinct aspects of plant development (Majer and Hochholdinger, 2011). Most LBD genes studied thus far are involved in aboveground development, including adaxial-abaxial patterning of Arabidopsis leaves (Lin et al, 2003), proximal-distal patterning in Arabidopsis petals (Chalfun et al, 2005), embryo sac and leaf development in maize (Evans, 2007), leaf expansion in Arabidopsis (Iwakawa et al, 2007), and glume formation in rice (Li et al, 2008). However, it has also been demonstrated that LBD genes are involved in different aspects of root formation, including lateral root formation in Arabidopsis (Okushima et al, 2007), shootborne root formation in rice (Inukai et al, 2005;Liu et al, 2005), and shoot-borne and seminal root initiation in maize (Taramino et al, 2007).…”
Section: Rtcs-dependent Regulation Of Lob Domain Genes and Transcriptmentioning
confidence: 99%